Hukum Hadhanah Anak Akibat Perceraian - Muhammad Hidayat; Tri Leli Rahmawati, Isyaq Maulidan (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2021)
Abstract: Children are a gift of God, so parents are obliged to take care of their children. When a divorce occurs, both parents still have obligations in taking care of their children. However, many parents do not take good care of their children. Based on this, this article examines the concept of hadhanah in Islamic law. This research is literature research and is descriptive analysis. Hadhanah is raising and educating children. Parents carry out hadhanah as a responsibility in fulfilling children's rights. The command of hadhanah is contained in al-Qur'an surat al-Baqarah verse 233 and at-Tahrim verse 6 that every Muslim should protect himself and his family from the fire of hell and always fear. In law number 1 of 1974 on marriage generally regulates the obligations of parents to their children in three articles, namely articles 45, 48, 49. In KHI, it is explained that the right of childcare will fall to the mother in the event of a divorce while the child has not been mumayyiz. The size of mumayyiz is if the child already can choose to go with his mother or father. Keywords: Hadhanah, child, parents, divorce, Islamic law. Abstrak: Anak merupakan karunia Allah Swt, maka orang tua berkewajiban memelihara anaknya. Bahkan ketika terjadi perceraian, kedua orang tua tetap memiliki kewajiban dalam mengurus anaknya. Namun, banyak orang tua yang tidak memelihara anaknya dengan baik. Berdasarkan hal tersebut, maka artikel ini mengkaji tentang konsep hadhanah dalam hukum Islam. Penelitian ini adalah penelitian pustaka dan bersifat deskriptif analisis.. Hadhanah atau memelihara dan mendidik anak dilaksanakan orang tua sebagai bentuk tanggung jawab dalam memenuhi hak anak. Perintah hadhanah termaktub dalam al-Qur’an surat al-Baqarah ayat 233 dan at-Tahrim ayat 6 bahwa setiap muslim harus memelihara diri dan keluarganya dari api neraka dan senantiasa bertakwa. Dalam undang-undang nomor 1 tahun 1974 tentang perkawinan secara umum mengatur kewajiban orang tua terhadap anaknya dalam tiga pasal yaitu pasal 45, 48, 49. Sedangkan dalam KHI dijelaskan bahwa hak pengasuhan anak akan jatuh kepada ibu apabila terjadi perceraian sedangkan anak belum mumayyiz. Ukuran mumayyiz adalah apabila anak sudah memiliki kemampuan untuk memilih ikut dengan ibunya atau ayahnya. Kata Kunci: Hadhanah, anak, orang tua, perceraian, hukum Islam.